Knowledge exchange, 'impact' and engagement: exploring low‐carbon urban transitions. Issue 3 (24th January 2013) - North, Peter
Abstract : This paper engages with recent discussions about new requirements for the consideration of the 'impact' of research by the UK research councils, and in the forthcoming Research Excellence Framework (REF). The paper argues that the need to consider impact should be critically welcomed, and, given that research is always subjectively evaluated, for academics to take a broad, rather than self‐limiting conceptionalisation of what constitutes impact in their research funding bids and submissions to the REF. The paper argues that the emerging Knowledge Exchange (KE) agenda provides a welcome mechanism for funding critically engaged research with real world partners on a participatory basis, and explores experiences of one such KE partnership, Low Carbon Liverpool, to discuss potentialities and problems.